Moderasi Beragama: Menangkal Islamophobia Melalui Revitalisasi Media Sosial - Kurniawan, Dandi; Afifi, Abdullah A (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2024)
Islamophobia has recently become more prevalent, both in the West and in Muslim nations. Social media contributes to the dissemination of anti-Islamic material. Religious moderation needs to find a way to moderate arising issues in society to avoid extremism, especially Islamophobia. This essay will look at ways to rejuvenate social media in an effort to combat Islamophobia. Using a qualitative methodology and analytical descriptive approaches, the core reasons for Islamophobia's growth and the ability of social media to combat it are investigated. According to the study's findings, Islamophobia is mostly caused by a misunderstanding of Islam and Muslim culture. Social media, when utilized wisely, has the ability to serve as a tool for public education about Islam, recovering its image as a religion of peace and salvation. The strategies that can be implemented include being moderate, critical, and responsive to Islamophobic content and educating about the wise use of social media. Active participation from all elements of society is needed to revitalize the role of social media in countering the negative impacts of Islamophobia and creating a better understanding in the middle of the community.